2015
DOI: 10.1038/srep13694
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-related protein 8 induces self-tolerance and cross-tolerance to bacterial infection via TLR4- and TLR2-mediated signal pathways

Abstract: Myeloid-related protein 8 (Mrp8) is the active component of Mrp8/14 protein complex released by phagocytes at the site of infection and stimulates inflammatory responses. However, it is unclear whether Mrp8 could induce self-tolerance and cross-tolerance to bacterial infection. Here we report that Mrp8 triggered TNF-α and IL-6 release via a Toll-like receptor 4 (TLR4)-dependent manner. Pre-stimulation of murine macrophages and human monocytes with Mrp8 induced self-tolerance to Mrp8 re-stimulation and cross-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…TNF-α, IL-1, and IL-6) production upon re-challenge with endotoxin (Erroi et al 1993; Granowitz et al 1993). This immune-regulatory process of induction is also associated with a unique metabolic phenotype in macrophages that facilitates persistent improvements in antimicrobial function (phagocytosis) against Gram-negative bacteria (Coveney et al 2015; Fensterheim et al 2017). Immediately following TLR stimulation, macrophages shift their metabolic profile to one that favors glycolysis over oxidative metabolism (Everts et al 2014) promoting a pro-inflammatory phenotype.…”
Section: The Importance Of Proteobacteria To Immune Education In Earlmentioning
confidence: 99%
“…TNF-α, IL-1, and IL-6) production upon re-challenge with endotoxin (Erroi et al 1993; Granowitz et al 1993). This immune-regulatory process of induction is also associated with a unique metabolic phenotype in macrophages that facilitates persistent improvements in antimicrobial function (phagocytosis) against Gram-negative bacteria (Coveney et al 2015; Fensterheim et al 2017). Immediately following TLR stimulation, macrophages shift their metabolic profile to one that favors glycolysis over oxidative metabolism (Everts et al 2014) promoting a pro-inflammatory phenotype.…”
Section: The Importance Of Proteobacteria To Immune Education In Earlmentioning
confidence: 99%
“…6,7 Ionita et al 8 have reported that Mrp8 and Mrp14 can form Mrp8/14 heterodimers that contribute to the formation of human atherosclerotic plaques. 10 Recently, accumulating evidence has strongly implied that soluble Mrp8/14 recruits neutrophils through TLR4 signaling pathway, which in turn, regulates slow neutrophil rolling and attachment to the vascular endothelium in a manner that was dependent on β2-integrin. Furthermore, Mrp8/14 can induce self-tolerance and cross-tolerance to cell infection through TLR2 and TLR4-mediated signaling pathways.…”
mentioning
confidence: 99%
“…Secondly, Experiment 1 used heat-treated LPS in Ringers, created by placing a random sample of the LPS aliquots into a heat block at 100°C for 30 minutes. Heat-treated LPS is commonly used as a control in immunological studies of mammals or mammalian cells, even though many of these studies subsequently find that heat treatment has no e ect on the immune-stimulating effect of LPS (Singh-Jasuja et al, 2000;Panjwani et al, 2002;Millar et al, 2003;Motojima et al, 2010;Coveney et al, 2015). We nevertheless included heat-treated LPS in Experiment 1 to test whether it might be a useful control in experiments on insects.…”
Section: Experimental Immune Challenge and Controlsmentioning
confidence: 99%